Intravenous Arginine Administration Downregulates NLRP3 Inflammasome Activity and Attenuates Acute Kidney Injury in Mice with Polymicrobial Sepsis - Sharon Angela Tanuseputero; Ming-Tsan Lin; Sung-Ling Yeh; Chiu-Li Yeh (Hindawi Limited, 2020)
Acute kidney injury (AKI) is a major complication of sepsis. Nucleotide-binding domain-like receptor protein 3 (NLRP3) inflammasomes are multiprotein complexes that mediate septic AKI. L-arginine (Arg) is a conditionally essential amino acid in catabolic conditions and a substrate for nitric oxide (NO) production; however, its use in sepsis is controversial. This study investigated the effect of intravenous Arg supplementation on modulating NLRP3 inflammasome activity in relation to septic AKI. Mice were divided into normal control (NC), sham, sepsis saline (SS), and sepsis Arg (SA) groups. In order to investigate the role of NO, L-N6-(1-iminoethyl)-lysine hydrochloride (L-NIL), an inducible NO synthase inhibitor, was administered to the sepsis groups. Sepsis was induced using cecal ligation and puncture (CLP). The SS and SA groups received saline or Arg via tail vein 1 h after CLP. Mice were sacrificed at 6, 12, and 24 h after sepsis. The results showed that compared to the NC group, septic mice had higher plasma kidney function parameters and lower Arg levels. Also, renal NLRP3 inflammasome protein expression and tubular injury score increased. After Arg treatment, plasma Arg and NO levels increased, kidney function improved, and expressions of renal NLRP3 inflammasome-related proteins were downregulated. Changes in plasma NO and renal NLRP3 inflammasome-related protein expression were abrogated when L-NIL was given to the Arg sepsis groups. Arg plus L-NIL administration also attenuated kidney injury after CLP. The findings suggest that intravenous Arg supplementation immediately after sepsis restores plasma Arg levels and is beneficial for attenuating septic AKI, partly via NO-mediated NLRP3 inflammasome inhibition.